Household-Level Effects of Energy Insecurity on Welfare in Southern Africa: A Malawian Case Study - Mkomba, Fydess Khundi; Saha, Akshay Kumar; Wali, Umaru Garba (International Journal of Renewable Energy Development, 2021)
The debate of energy security has, over the past decades, centered on supply factors within the energy policy framework in the public policy discourse. Much more empirical evidence is required to fully understand  the household-level effects of energy security on development outcomes. This paper explores the  characteristics of the households that face energy insecurity and also analyze the effects of energy insecurity on household welfare using the recent data from the Malawi Fourth Integrated Household Survey(IHS4) 2016-2017. Overall, 42.58% of Malawian households were found to be  energy insecure and the study findings show that the energy insecure were a heterogenous group compared to the energy secure. The heterogeneity exist because  of differences in demographics (likely to be advanced in age, likely to be females,  less likely to have a household head  with  formal education); socioeconomic status (likely to be poor,  had low wealth  levels); geography (likely to be rural dwellers in the central and southern parts of Malawi); housing and dwelling status (less likely to be renters, less likely to be found in permanent or semi-permanent buildings that have iron sheets and cement floor). Additional results from econometric analysis showed that energy insecure households reduced their food consumption by 2.3% for each 1% unit increase in the share of the energy costs in their total household budget. Similarly, on the education outcome, the energy insecure households reduced  their education expenditure by 3.6% for each 1% unit increase in the share of the energy costs over the total household expenditure. These findings show that energy security plays a key role towards improvement of household welfare in general as this might have short term and long-term negative implications on human capital development.